Predicting Problem-Solving Ability through Self-Confidence and Thinking Styles among Indonesian Islamic Senior High School Students - Ahmad, Ismail; Permana, Andi (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2025)
This study examines the extent to which self-confidence and thinking styles predict problem-solving ability among students in Indonesian Islamic senior high schools. Using a quantitative predictive-correlational design, the study involved 73 students from three state Islamic senior high schools in Ciamis, West Java, Indonesia, namely Madrasah Aliyah Negeri 2 Ciamis, Madrasah Aliyah Negeri 3 Ciamis, and Madrasah Aliyah Negeri 6 Ciamis. Data were collected using questionnaires to measure self-confidence and thinking styles, while students’ problem-solving ability was assessed through an observation checklist. The data were analyzed using descriptive statistics, correlation analysis, and multiple regression analysis. The findings show that self-confidence has a positive relationship with problem-solving ability, with a correlation coefficient of r = 0.573. Thinking styles also show a positive relationship with problem-solving ability, with r = 0.615. Simultaneously, self-confidence and thinking styles have a stronger relationship with problem-solving ability, with r = 0.749. These findings suggest that problem-solving ability is shaped by both affective and cognitive dimensions. The study implies that Islamic senior high schools need to strengthen students’ confidence and develop flexible thinking through reflective, collaborative, problem-based, and value-oriented learning.